Diagnosing Herbicide Injury in Corn - Sarah Berger; Jason Ferrell; Peter Dittmar (EDIS, 2013)
This 9-page fact sheet lists nine modes of action: the mechanism of action, behavior in plants, symptoms and herbicides, and illustrations. Written by Sarah Berger, Jason Ferrell, and Peter Dittmar, and published by the UF Department of Agronomy, January 2013.